Adolescent pregnancy termination and childbearing – the impact of an older sister’s pregnancy outcome: IJPDS (2017) Issue 1, Vol 1:031, Proceedings of the IPDLN Conference (August 2016) - Wall-Wieler, Elizbaeth; Roos, Leslie; Nickel, Nathan (International Journal of Population Data Science, 2017)
ABSTRACT Background An older sister's teenage pregnancy status is known to influence whether or not a younger sister also has a teenage pregnancy. This study examines whether a younger sister’s odds of teenage pregnancy are impacted by her older sister’s teenage pregnancy status (no pregnancy, teenage mother, termination), and if she does become pregnant, if the older sister’s teenage pregnancy status impacts her odds of terminating that pregnancy. Methods A birth cohort created with the linkable administrative databases housed at the Manitoba Centre for Health Policy (MCHP) is used to examine these questions. The cohort consisted of 17,169 teenage girls born in Manitoba between April 1, 1979 and March 31, 1994, who stayed in the province until at least their 20th birthday, had at least one older sister, and were not missing values on any key variables. Logistic regression models, controlling for a variety of confounders, are used to examine the relationship between sisters’ teenage pregnancy outcomes. First, the relationship between an older sister’s teenage pregnancy status (no teenage pregnancy, terminated teenage pregnancy, and teenage mother) and a younger sister’s teenage pregnancy is examined. Second, for those who had a teenage pregnancy, the likelihood of her terminating that pregnancy is examined based on her older sister’s teenage pregnancy status. Results Teenagers whose older sister had been a teenage mother (OR = 3.2; 95% CI 2.8-36) and those whose older sister terminated her teenage pregnancy (OR= 2.6; 95% CI 2.2-3.0) had significantly higher odds of having a teenage pregnancy than those whose older sister did not have a teenage pregnancy. For those who did have a teenage pregnancy, termination of that pregnancy was more likely if she had an older sister who terminated her teenage pregnancy (OR = 2.7; 95% CI 1.9-3.7) or did not have a teenage pregnancy (OR = 1.8; 95% CI 1.3-2.4) than if her older sister was a teenage mother. Conclusion An older sister's teenage pregnancy outcome has a significant impact on whether or not a younger sister becomes pregnant and whether she terminates her teenage pregnancy. Younger sisters are most likely to become pregnant if their older sisters had been teenage mothers; these girls were also least likely to terminate their teenage pregnancy.